Pendekatan Public Relations Politik di Media Sosial dalam Pembentukan Citra Politik - Anggie Ayu Astria Latuperissa (LPPM Universitas Bina Sarana Informatika, 2022)
The study of political communication in the formation of political images using social media tools is still very limited, for this reason this research was conducted in order to see the phenomenon of the use of social media by politicians in shaping their political image. By examining the pattern of reciprocal relationships between netizens and politicians in this context, the 2017-2022 Governor of DKI Jakarta was elected, Anies Rasyid Baswedan, in the @aniesbaswedan Instagram account. The method used in this research is an intrinsic qualitative case study, with the support of content search in the form of relevant images and text, as well as interview techniques to produce descriptions to describe the relationships that are built between netizens and the government or politicians. The findings of this study include three major themes in shaping Anies' image, namely performance reputation, religion (Islam), and personal politics that form the pattern of communication relationships between Anies Baswedan and netizens (social media users) reciprocally through Instagram social media or communication patterns. secondary and can be classified into five typologies of netizens in responding to Anies' uploads, which each have their own characteristics. In addition, there is also a description of the Political Public Relations approaches used by Anies in uploads to the @aniesbaswedan account in forming a self-image. Keywords: Political public relations, political communication, social media, political image formation.